Development of a multiplex real-time PCR for the simultaneous detection of monkeypox virus clades I, II, and goatpox virus - Lin, Yongqiang; Guo, Zijing; Chen, Jinsong; Zhang, Xianwen; Zhou, Long; Li, Yanmin; Zhang, Zhidong (Frontiers in Veterinary Science, 2024)
IntroductionMonkeypox virus (MPXV) hosts are of multiple species, with a risk of cross-species transmission. This phenomenon poses a threat to unreported affected domestic animals and increases the risk to human public health. Clinical diagnostics continue to face challenges regarding specificity among poxviruses. The need for a rapid and precise assay to differentiate between MPXV clades I and II, as well as goatpox virus (GTPV) is essential for enhancing our capacity for disease prevention, control, and epidemiological investigation.MethodsTo address this need, we have successfully developed a multiplex real-time PCR assay targeting MPXV D14L gene for clade I, MPXV D18L gene for clade II, and GTPV RPO30 gene, which can simultaneously detect MPXV clades I and II as well as GTPV.ResultsThe developed assay demonstrated high sensitivity, with limits of detection at 207.83 copies/reaction for MPXV clade I, 252.07 copies/reaction for MPXV clade II, and 208.72 copies/reaction for GTPV. Importantly, there was no cross-reactivity with other non-pox viruses which infect goats. The assay exhibited excellent repeatability, with coefficients of variation (CV%) for intra-assay and inter-assay ranging from 0.17% to 0.89% and 0.58% to 1.09%, respectively.DiscussionThis assay can serve as a vital resource to safeguard against the MPXV epidemic posing a threat to the life safety of goats, to mitigate potential risks to the sheep farming industry, and to prevent the transmission of MPXV to humans through sheep, which could act as a potential transmission vector for infection.